ChemInform Abstract: ′On‐water′ Organic Synthesis: A Green, Highly Efficient, Low Cost and Reusable Catalyst System for Biaryl Synthesis under Aerobic Conditions at Room Temperature. Issue 43 (October 2015) - Saikia, Bishwajit; Boruah, Preeti Rekha; Ali, Abdul Aziz; Sarma, Diganta
Abstract The applied catalyst system can be reused at least five times without significant loss of activity.